IMPROVING CHILDREN VERBAL LANGUAGE COMPETENCE THROUGH STORY TELLING USED VISUAL AUDIO MEDIA (PIAUD IAIN Kudus, 2021)
The Goal is to describe storytelling method through visual audio to improve verbal language competence and to know the result of using storytelling method through visual audio media. This study applied an action research with two variables, verbal language competence and storytelling with audio-visual media. The steps used were: Planning. Acting, Observing, and Reflecting. The subject was children of PAUD Alam Jungle School Consisted of 13 girls and 7 boys. The result showed that storytelling through visual audio media contributes significantly to the children’ verbal communication improvement. It can be seen from the cycle I reach 50 % (10 children) in category undeveloped, starting develop is 40 % (8 children), and 10 % (2 children) in category undeveloped. The cycle II showed that children on category developed properly are 85 % (17 children) and category starting develops is 15 % (3 children).